The relationship between histopathology and age factor in patients who were operated for renal masses - Yıkılmaz, Taha Numan (Turk J Urol, 2015)
OBJECTIVE: Renal neoplasms have a predilection to occur in older patients and they are often malignant. They may have different structural characteristics according to age groups. In our study, we have investigated age-related demographic characteristics of the patients who were operated because of suspected malignant renal masses. MATERIALS AND METHODS: Between 2010 and 2014, 129 patients were treated surgically for suspected malignant renal masses at our institution. These cases had undergone open radical, open partial, and laparoscopic radical nephrectomies. Patients were divided into two groups based on their ages and evaluated accordingly as Group 1 (≤50 years) and Group 2 (>50 years). Groups were compared based on their clinical and pathological features. RESULTS: Group 1 and Group 2 consisted of 29 (22.4%) and 91 (77.6%) patients, respectively. The mean age of younger patients was 43.1 years (23–49 years), with a male to female ratio of 19/10, while the average tumor size was 57.6 mm (20–120 mm). Twenty-four patients (83%) had a malignant pathology and five patients (17%) had a benign pathology. Clear cell carcinoma was diagnosed in 67% of the patients in both groups. There was no significant difference with respect to age and tumor size of male and female patients in the younger age group, while younger female adults tended to have a more benign pathology than their male counterparts (40% and 5%, respectively, p<0.05). CONCLUSION: There was no significant difference with respect to gender, tumor size, laterality, and surgical and pathologic features between younger and older patients. An organ- sparing approach should be strongly considered when treatment for renal tumors in young females is performed because of a potentially higher incidence of a benign pathology of renal masses.